1996
DOI: 10.1007/bf02509540
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform infrared spectroscopy of the solution-mediated conversion of amorphous calcium phosphate to hydroxyapatite: New correlations between X-ray diffraction and infrared data

Abstract: Fourier Transform infrared spectroscopic analysis of maturing, poorly crystalline hydroxyapatite (HA) formed from the conversion of amorphous calcium phosphate (ACP) at constant pH or variable pH show only subtle changes in the v1, v3 phosphate absorption region (900 cm-1-1200 cm-1). This region is of interest because it can be detected by analysis of mineralized tissue sections using FT-IR microscopy. To evaluate the subtle spectral changes occurring during the maturation, second derivatives of the spectra we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
161
2
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(181 citation statements)
references
References 28 publications
10
161
2
4
Order By: Relevance
“…PBSu is a typical semicrystalline polymer with two characteristic peaks at 2& 19.8 and 22.6° while the features of interest consists of a broad contour between 2& = 27-37° resulting from the 002 reflection of hydroxyapatite. New peaks are observed at 2& 32,4 36,45 and 46° after immersion in SBF which confirm that partially crystallized apatite layer formed on the surfaces of PBSu film as well as on its nanocomposites [33,37,38].…”
Section: In Vitro Bioactivity Testmentioning
confidence: 58%
“…PBSu is a typical semicrystalline polymer with two characteristic peaks at 2& 19.8 and 22.6° while the features of interest consists of a broad contour between 2& = 27-37° resulting from the 002 reflection of hydroxyapatite. New peaks are observed at 2& 32,4 36,45 and 46° after immersion in SBF which confirm that partially crystallized apatite layer formed on the surfaces of PBSu film as well as on its nanocomposites [33,37,38].…”
Section: In Vitro Bioactivity Testmentioning
confidence: 58%
“…6). It has been reported that a peak near 1020 cm −1 is attributed to the ν 3 vibration of PO 4 3− in non-stoichiometric apatites but a peak at 1030 cm −1 is indicative of the ν 3 vibration of PO 4 3− in stoichiometric apatites [14,15]. Both peaks appeared in the second-derivative IR spectra of the calcified sample of tendon, suggesting the mineralization is still in progress.…”
Section: Discussionmentioning
confidence: 96%
“…Figure 5b shows several unique peaks at 1153, 1012, 989, 956 and 873 cm −1 in the IR spectrum of sample b. The IR peaks at 1153, 1012 and 989 cm −1 were assigned to the brushite (CaHPO 4 · 2H 2 O), which was believed to be a precursor of apatite [15,42]. The peaks at 956 and 873 cm −1 corresponded to the ν 1 PO 4 3− of HA and carbonate ions located in PO 4 3− sites of HA [14,15,19,42].…”
Section: Discussionmentioning
confidence: 99%
“…[18], carbonate-phosphate ratio (890 -850 cm -1 / 1200 -900 cm -1 ) [19], crystallinity (1030/1020 cm -1 ) [20,21], collagen maturity (1660/1690 cm -1 ) [22] and acid phosphate (1127/1096 cm -1 ) [23]. Furthermore, the spatial heterogeneity of each parameter was determined from the full width of half maximum (FWHM) of the Gaussian curve fitted to the pixel histogram of the measured area [24].…”
Section: Ftirmentioning
confidence: 99%